2013
DOI: 10.3390/ijms14023639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Enhanced Stability of R(+)-Alpha Lipoic Acid by the Complex Formation with Cyclodextrins

Abstract: R(+)-alpha lipoic acid (RALA) is one of the cofactors for mitochondrial enzymes and, therefore, plays a central role in energy metabolism. RALA is unstable when exposed to low pH or heat, and therefore, it is difficult to use enantiopure RALA as a pharma- and nutra-ceutical. In this study, we have aimed to stabilize RALA through complex formation with cyclodextrins (CDs). α-CD, β-CD and γ-CD were used for the formation of these RALA-CD complexes. We confirmed the complex formation using differential scanning c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 21 publications
8
51
0
Order By: Relevance
“…Since the stability of αLA is affected by exposure to acid, ultraviolet light, or oxygen, the stabilization of R-αLA is important for its industrial use. A complex between αLA and γCD is known to be more stable in the stomach or intestines of a living body than free αLA [7]. We subsequently reported that the anti-diabetic effects of racemic-αLA/γCD were stronger than those of free racemic-αLA.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Since the stability of αLA is affected by exposure to acid, ultraviolet light, or oxygen, the stabilization of R-αLA is important for its industrial use. A complex between αLA and γCD is known to be more stable in the stomach or intestines of a living body than free αLA [7]. We subsequently reported that the anti-diabetic effects of racemic-αLA/γCD were stronger than those of free racemic-αLA.…”
Section: Discussionmentioning
confidence: 92%
“…The preparation of αLA/γCD complexes was done as previously described [7]. R-, S-, or racemic-αLA was dissolved in deionized water, in which the pH was monitored, and a corresponding molar amount of γCD was added for a 1:1 ratio.…”
Section: Preparation Of Racemic- R- and S-αla/γcd Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample injection volume was 20 lL and mobile phase was at a flow rate of 1.2 mL/ min. The EGCG and ALA were detected by the wavelength of 280 and 215 nm, respectively, and the temperature of column oven was maintained at 30°C [32,33].…”
Section: High-performance Liquid Chromatography Analysismentioning
confidence: 99%
“…These complexes have been exploited to enhance material properties, especially the solubility, stability, and bioavailability of drugs. 12,[17][18][19]21,22 Over 35 different drugs are currently being marketed globally as solid or solution-based CD complex formulations. 20,23,24 Cyclodextrins form inclusion complexes with drug molecules in solution and solid states as described above, and the CDdrug inclusion complexes are well known to be prepared in the presence of water molecules.…”
Section: Introductionmentioning
confidence: 99%